Systolic blood pressure target: Have we identified the optimal target yet? - Elgendy, Islam Y.; Pepine, Carl J. (Journal of Public Health and Emergency; Vol 1 (June 2017): Journal of Public Health and Emergency, 2017)
Systemic hypertension remains the leading modifiable risk factor for the global burden of disease (1). Over the past five decades, we have identified effective therapeutic interventions to further reduce the risks associated with poorly controlled hypertension. However, the optimal systolic blood pressure (SBP) “target” has been a matter of ongoing debate. This debate has been reflected in recommendations by various groups. For example, the former members of the Eighth Joint National Committee Panel recommended a therapeutic SBP target